Relation between oral health and nutritional condition in the elderly - Humberto Lauro Rodrigues Junior; Miriam F. Zaccaro Scelza; Gilson Teles Boaventura; Silvia Maria Custódio; Emília Addison Machado Moreira; Diane de Lima Oliveira (University of São Paulo, 2012)
Oral health is a prerequisite for a good chewing function, which may have an impact on food choices and nutritional well-being. OBJECTIVE: This study was designed to evaluate the relationship between oral health status and nutritional status in the elderly. MATERIAL AND METHODS: In this cross-sectional study, 33 elderly people from the Group for the Elderly Interdisciplinary Geriatrics and Gerontology Program, at Fluminense Federal University, Niteroi, RJ, Brazil, completed a questionnaire to collect information on socioeconomic status, eating habits, physical activity and health habits, undertook a clinical oral examination, blood test, and anthropometric measurements, and were allocated into groups according to age. The oral health status was assessed using the index for decayed, missing and filled teeth (DMFT). The nutritional status was assessed using hemoglobin, hematocrit and albumin concentrations in blood, anthropometric values and the body mass index. RESULTS: Tooth loss was the biggest nuisance to the elderly subjects (57.6%), followed by the use of dentures (30.3%) and ill-fitting dentures (33.3%). 66.6% of patients had difficulty in chewing, and 54.5% reported this to be due to prostheses and 13.6% to the absence of teeth. A significant correlation was found between DMFT and the value of suprailiac skinfold thickness (rho=0.380, p=0.029). CONCLUSION: The results support the temporal association between tooth loss and detrimental changes in anthropometry, which could contribute to increased risk of developing chronic diseases.